Hypothermia and its role in patients with ST-segment-elevation myocardial infarction and cardiac arrest - Keller, Karsten; Sagoschen, Ingo; Schmitt, Volker H.; Münzel, Thomas; Gori, Tommaso; Hobohm, Lukas (Frontiers in Cardiovascular Medicine, 2022)
Background Patients with cardiac arrest due to ST-segment-elevation myocardial infarction (STEMI) are at very high risk to die. Besides reperfusion strategies, therapeutic hypothermia is recommended in patients who remain unconscious after resuscitation driven by cardi-ac arrest. However, data analysing the impact of therapeutic hypothermia on survival showed inconsistent results. We aimed to investigate benefits of therapeutic hypo-thermia in STEMI patients with cardio-pulmonary resuscitation. Methods Patients with STEMI and cardio-pulmonary resuscitation (CPR) were identified by screening the German nationwide inpatient sample (2005-2019). These patients were stratified for therapeutic hypothermia. Impact of hypothermia on mortality and adverse in-hospital outcomes was analysed. Results Overall, 133,070 hospitalizations of patients with STEMI after cardiac arrest (53.3% aged ≥70 years; 34.0% females) were recorded in Germany between 2005-2019, of which 12.3% (16,386 patients) underwent therapeutic hypothermia. Females (23.8% vs. 35.4%, P<0.001) and patients aged ≥70 years (34.9% vs. 55.9%, P<0.001) were less frequently treated with therapeutic hypothermia. In-hospital case-fatality rate was lower in STEMI with CPR and subsequent hypothermia compared to treatment without hypothermia (53.5% vs. 66.7%, P<0.001). Therapeutic hypothermia was independently associated with reduced in-hospital case-fatality rate (OR 0.83 [95%CI 0.80-0.86], P<0.001). In addition, therapeutic hypothermia was associated with an increased risk for stroke (OR 1.37 [95%CI 1.25-1.49], P<0.001), pneumonia (OR 1.75 [95%CI 1.68-1.82], P<0.001) and acute kidney injury (OR 2.21 [95%CI 2.07-2.35], P<0.001). Conclusions Therapeutic hypothermia was associated with a survival benefit in STEMI patients af-ter cardiac arrest.